Physico-chemical Characteristics of Pomegranate (Punica granatum L.) Selections from Southeastern Turkey - KAZANKAYA, A.; GUNDOGDU, M.; DOGAN, A.; FIKRET BALTA, M.; CELIK, F. (Asian Journal of Chemistry, 2010)
This paper deals with desirable physico-chemical characteristics of pomegranate (Punica granatum L.) genetic resources of Siirt province (southeastern Anatolia, Turkey) during 2002 and 2004. Twenty five genotypes were selected as promising in the existing population of pomegranate and they were described with respect to fruit attributes in order to conserve valuable native germplasm of pomegranate and to identify them for future breeding efforts. Genotypes averagely had a range of 234-332 g for fruit weight, 76-83 mm for fruit diameter, 68-81 mm for fruit length, 217-333 cm3 for fruit volume, 0.86-1.31 fruit density (g/cm3), 0.87-1.00 for fruit shape index, 19.1-21.9 mm for calyx high, 12.9-16.0 mm for calyx diameter, 86-120 mL for fruit juice volume, 37.4-45.7 g for total seed weight, 52.3-62.5 % for seed percentage, 20-66 % for pink coloured skin percentage, 2.5-3.7 mm for skin thickness, 17-22 % for soluble solids, 3.2-3.8 for pH, 0.7-1.0 % for acidity and 18-76 mg/100 g for vitamin C. Fruits of genotypes contained a range of 168-672 ppm in N, 72-301 ppm in P, 856-4423 ppm in K, 10-93 ppm in Na, 38-74 ppm in Ca, 39-98 ppm in Mg, 1.5-9.2 ppm in Fe, 1.8-9.6 ppm in Zn, 0.1-4.4 ppm in Mn and 0.5-4.2 ppm in Cu. In addition, they had easy separated seeds. Their seed hardness was hard, soft, semi-hard and seed colours were pink, light-pink and red.